Folter und Terrorismus. Die Aufweichung des absoluten Folterverbots in Theorie und Praxis. - David Hasenauer (Historia.scribere)
Torture and terrorism. The softening of the absolute prohibition of torture in theory and practice. This seminar-paper deals with society’s handling of torture in conjunction with modern terrorism, especially after 9/11. Even if torture is abolished and outlawed by several international rights, there were and there are some hypothetical scenarios, in which torture seems to be justifiable – at least from moral views. How states and sociologists deal with these scenarios in reality and how particularly the US.-government handles the threat of terrorism with or without torture is going to be cleared in this paper.